(untitled) (Clinics, 2013)
OBJECTIVES: Medical and surgical intensive care unit patients represent two different populations and require different treatment approaches. The aim of this study was to investigate the parameters associated with mortality in medical and surgical intensive care units. METHODS: This was a prospective cohort study of adult patients admitted to a medical and surgical intensive care unit teaching hospital over an 11-month period. Factors associated with mortality were explored using logistic regression analysis. RESULTS: In total, 827 admissions were observed, and 525 patients >;18 years old and with a length of stay >;24 h were analyzed. Of these patients, 227 were in the medical and 298 were in the surgical intensive care unit. The surgical patients were older (p